Cribra orbitalia: Prevalence in contemporary populations. Issue 7 (7th June 2016) - Steyn, Maryna; Voeller, Sarah; Botha, Deona; Ross, Ann H.
Abstract : The prevalence of cribra orbitalia (CO) is often used as an indicator of the general health status of past populations. Although debates as to its exact etiology are still ongoing, cribra is generally accepted to be the result of an anemic condition. Cribra has been reported to be declining in modern populations or even to be absent. The aim of this study was to compare modern, historic, and prehistoric prevalences of CO to assess whether it has changed through time and if it still occurs in contemporary populations. CO in skeletons ( n  = 844) from two widely different regions, the northeastern US and the central Gauteng area of South Africa, were compared in order to evaluate temporal trends. The sample comprised 245 prehistoric, 381 historic, and 218 modern skeletons. In adult skeletons the prevalence was found to be lower in historic South Africans (2.23%) than in historic North Americans (6.25%). It was lower in modern North Americans than in modern South Africans (12.35 and 16.8%, respectively). Its prevalence in prehistoric North Americans (11.86%) was also not much different from that of modern North Americans (12.35%). The frequency of CO in historic South African juveniles was higher (10.71%) than in historic North American juveniles (1.35%). Modern South African children had a lower frequency (25.14%) than modern American juveniles (40%), although the sample in the North American group was small. It seems that CO is still present in modern populations, and that health may indeed have declined for some groups in recent times. Clin. Anat. 29:823–830, 2016. © 2016 Wiley Periodicals, Inc.